Business ethics: A literature review with a focus on marketing ethics - Tsalikis, John (Journal of business ethics, 1989)
In recent years, the business ethics literature has exploded in both volume and importance. Because of the sheer volume and diversity of this literature, a review article was deemed necessary to provide focus and clarity to the area. The present paper reviews the literature on business ethics with a special focus in marketing ethics. The literature is divided into normative and empirical sections, with more emphasis given to the latter. Even though the majority of the articles deal with the American reality, most of the knowledge gained is easily transferable to other nations.